Deep learning for decentralized parking lot occupancy detection. (15th April 2017) - Amato, Giuseppe; Carrara, Fabio; Falchi, Fabrizio; Gennaro, Claudio; Meghini, Carlo; Vairo, Claudio
Highlights: We propose an effective CNN architecture for visual parking occupancy detection. The CNN architecture is small enough to run on smart cameras. The proposed solution performs and generalizes better than other SotA approaches. We provide a new training/validation dataset for parking occupancy detection. Abstract: A smart camera is a vision system capable of extracting application-specific information from the captured images. The paper proposes a decentralized and efficient solution for visual parking lot occupancy detection based on a deep Convolutional Neural Network (CNN) specifically designed for smart cameras. This solution is compared with state-of-the-art approaches using two visual datasets: PKLot, already existing in literature, and CNRPark-EXT. The former is an existing dataset, that allowed us to exhaustively compare with previous works. The latter dataset has been created in the context of this research, accumulating data across various seasons of the year, to test our approach in particularly challenging situations, exhibiting occlusions, and diverse and difficult viewpoints. This dataset is public available to the scientific community and is another contribution of our research. Our experiments show that our solution outperforms and generalizes the best performing approaches on both datasets. The performance of our proposed CNN architecture on the parking lot occupancy detection task, is comparable to the well-known AlexNet, which is three orders of magnitude larger.